Lesser Known Facts of Small Cell Lung Cancer. Issue 4 (July 2019) - Li, Xin; Enzerra, Michael; Smith, Daniel Arnold; Rahnemai-Azar, Amir Ata; Kikano, Elias; Ramaiya, Nikhil H.
Abstract : Abstract: Until recently, the treatment of small cell lung cancer (SCLC), a malignancy classically described as having a robust response to first-line therapy with near-universal recurrence, has remained relatively unchanged. Advancements in the management of SCLC have lagged behind those seen for non–small cell lung cancers. As the era of precision medicine and targeted immunotherapy evolves, radiologists must be familiar with the modern treatment paradigms of SCLC and associated imaging patterns, including classic and nonclassic appearances of treatment complications.